How to use Gliricidia sepium for pest management - Gosling, Amanda; Center for International Forestry Research and World Agroforestry (2024)
This poster illustrates the different ways that Gliricidia sepium can be used for pest management. It explains how to make a Gliricidia leaf extract and apply it with a modified plastic bottle, the pest management benefits of planting Gliricidia hedgerows and using the leaves in grain storage areas. It encourages farmers to regularly scout for pests and to keep records. It also gives some general safety procedures for preparing and applying homemade extracts. The poster forms part of the Climate-Smart Forage and Feed Innovations training package that was co-developed with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) Tanzania and Malawi teams to accelerate the spillover process of validated AICCRA technologies. The poster content is based on knowledge materials sourced from the AICCRA Zambia team and their respective project partners (Community Markets for Conservation (COMACO) and Mediae.